The Prevalence of Hypertension and Associated Risk Factors among Secondary School Teachers in Bahir Dar City Administration, Northwest Ethiopia - Destaw Damtie; Ayehu Bereket; Denekew Bitew; Bizuayehu Kerisew (International Journal of Hypertension)
Background. Hypertension is one of the noncommunicable cardiovascular diseases (CVDs), and its prevalence is rising in middle- and low-income countries. It is not given enough attention in the developing countries like Ethiopia. Not enough data and studies about hypertension are available in Ethiopia. This study aimed to determine the prevalence of hypertension and its associated risk factors among secondary school teachers in Bahir Dar city administration. Methods. An institutional-based cross-sectional survey was conducted among secondary school teachers in Bahir Dar. Two hundred twenty-two randomly selected teachers were interviewed, and data related to the demographic, behavioral, health, and dietary characteristics of the individuals were recorded. Blood pressure data were taken. Logistic regression analysis had been used to assess independent risk factors for hypertension. p-values of less than 0.05 were considered statistically significant. Results. The overall prevalence of hypertension in the study was 29.28%. Age 41 to 50 (AOR: 2.506; 95% CI: 1.103–5.694; and p=0.028), having self-reported diabetes mellitus (AOR: 8.595; 95% CI: 2.795–26.424; and p<0.0001), having a family history of hypertension (AOR: 3.387; 95% CI: 1.579–7.285; and p=0.002), khat chewing (AOR: 5.426; 95% CI: 1.811–16.256; and p=0.003), physical inactivity (AOR: 5.212; 95% CI: 1.974–13.763; and p=0.001), and presence of self-reported repeated stress (AOR: 3.027; 95% CI: 1.404–6.527; and p=0.005) were the risk factors associated with hypertension. Conclusions. Different intervention measures with a particular emphasis on prevention by introducing lifestyle modifications are highly recommended to mitigate and control hypertension.